Control of Toxicity of Sarcocystis fayeri in Horsemeat by Freezing Treatment and Prevention of Food Poisoning Caused by Raw Consumption of Horsemeat - HARADA, Seiya; SAITO, Morihiro; MATSUMOTO, Hiroshi; WATANABE, Maiko; SUGITA-KONISHI, Yoshiko; IRIKURA, Daisuke; YAHIRO, Shunsuke; TOKUOKA, Eisuke; MATSUMOTO, Kazutoshi; MIYASAKA, Jiro; KAMATA, Yoichi; FURUKAWA, Masato (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2013)
More than 27 outbreaks per year of food poisoning caused by consuming horse meat were reported in Kumamoto Prefecture (including Kumamoto City) from January 2009 to September 2011. It was found that the causative agent of the outbreaks was a protein with a molecular weight of 15 kDa that had originated from bradyzoites of Sarcocystis fayeri parasitizing the horse meat. Rabit ileal loop tests showed that pepsin treatment of homogenates of frozen horse meat containing the cysts of S. fayeri induced loss of toxicity, presumably by digestion of the proteinous causative agent(s). Slices of horse meat containing the cysts were frozen at below -20°C for various periods. The cysts were collected after thawing the slices, then treated in an artificial stomach juice containing pepsin. The bradyzoites of the cysts kept at -20°C for 48 hr or more completely disappeared. Simultaneously, the 15 kDa protein also disappeared in the frozen cysts. After notifying the public and recommending freezing treatment of horse meat, no subsequent cases of food poisoning were reported. This indicates that freezing of horse meat is effective to prevent the occurrence of food poisoning caused by consuming raw horse meat containing S. fayeri.